H-ras inhibits the hippo pathway by promoting Mst1/Mst2 heterodimerization - Rawat, Sonali J. (Curr Biol, 2016)
The protein kinases Mst1 and Mst2 have tumor suppressor activity, but their mode of regulation is not well established. Mst1 and Mst2 are broadly expressed and may have certain overlapping functions in mammals, as deletions of both Mst1 and Mst2 together are required for tumorigenesis in mouse models [1–3]. These kinases act via a three-component signaling cascade comprising Mst1/2, the protein kinase Lats1/2, and the transcriptional coactivators Yap and Taz [4–6]. Mst1/2 contain C-terminal SARAH domains that mediate their homodimerization as well as heterodimerization with other SARAH-domain containing proteins, which may regulate Mst1/2 activity. Here, we show that, in addition to forming homodimers, Mst1 and Mst2 heterodimerize in cells, that this interaction is mediated by their SARAH domains and is favored over homodimers, and that these heterodimers have much reduced protein kinase activity compared to Mst1 or Mst2 homodimers. Mst1/Mst2 heterodimerization is strongly promoted by oncogenic H-ras, and this effect requires activation of the Erk pathway. Cells lacking Mst1, in which Mst1/Mst2 heterodimers are not possible, are resistant to H-ras-mediated transformation and maintain active hippo pathway signaling compared to wild-type cells or cells lacking both Mst1 and Mst2. Our results suggest that H-ras, via an Erk-dependent mechanism, down-regulates Mst1/2 activity by inducing the formation of inactive Mst1/Mst2 heterodimers.